Dynamic modeling of a stand - alone pem fuel cell connected to adjustable speed drive - Zambri, Nor Aira (2009)
Fuel cell has a good potential as a stand-alone generation system and as energy supplied to Adjustable Speed Drive (ASD) model. This is because of its low operation temperature (70°C until 90°C) and also it has a good dynamic response. In this project, Proton Exchange Membrane (PEM) fuel cell is used as energy source. Dynamic modeling of a stand-alone PEM fuel cell which connected to several types of ASD system had been modeled by using Matlab/Simulink software. The PEM fuel system has several important sections, namely, fuel cell controller, fuel cell and power conditioning unit. Integrated and proportional controllers are used to control the fuel cell or the hydrogen flow rate that enters the PEM fuel cell. Simulation results show that fuel cell output power can fulfill the load demand in a short duration. Single-phase ASD and three-phase ASD are reviewed as loads in this project and their individual harmonics are investigated based on simulation results. Results also show that ASD generates harmonics to the line voltage and current. A method to reduce harmonics distortion in a network of ASD is proposed in this project. As a result, by combining different types of ASD as network, significant reduction on total harmonics distortion can be obtained.